2005
DOI: 10.35197/rx.01.03.2005.07.jn
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades físicas y mecánicas de la madera en Quercus laeta Liemb. de El Salto, Durango.

Abstract: En este trabajo se dan a conocer resultados obtenidos en los ensayos físicos y mecánicos en la madera de Quercus laeta Liemb. de la región de El Salto, Durango. Los ensayos físicos y mecánicos se realizaron conforme a las normas COPANT (Comisión Panamericana de Normas Técnicas) siendo estos: densidad, contracción, punto de saturación de la fibra (PSF) y relación de anisotropía (RAN). Los ensayos mecánicos evaluados fueron: compresión perpendicular y paralela a la fibra, flexión estática, tensión perpendicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Our result (0.64 g cm À3 ) falls within this range, although near the lower value. Regarding Q. laeta values reported in the literature vary between 0.68 g cm À3[48] and 0.75 g cm À3[47]. Our result (0.58 g cm À3…”
supporting
confidence: 39%
“…Our result (0.64 g cm À3 ) falls within this range, although near the lower value. Regarding Q. laeta values reported in the literature vary between 0.68 g cm À3[48] and 0.75 g cm À3[47]. Our result (0.58 g cm À3…”
supporting
confidence: 39%
“…Experimentally, no changes in dimensions or deformation of samples was observed. Nájera-Luna et al, reported that the saturation point of white oak fiber was 30.1% moisture content [56]. Water absorption in WPCs is an important quality indicator because these materials absorb less moisture and do so more slowly than wood.…”
Section: Compositesmentioning
confidence: 99%
“…The fiber saturation point (FSP) is established at 30.1% moisture content. The anisotropy ratio (ANR) is 1.74, classified as high, indicating low dimensional stability of the wood [56].…”
Section: Introductionmentioning
confidence: 99%